Optimization of Turning Process By Using Taguchi Method - Harun Yaka; Harun Akkuş (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, AISI 1040 steel is machined on CNC lathes. TaguchiL16 ortogonal array was used as experimental design. Experimentswere carried out with selected the three cutting parameters. These parameterswere determined as feed rate, cutting speed and cutting depth. Turningoperation was carried out in dry conditions with diamond cutting tools. At theend of experiments, the values of surface roughness (Rz) on samples were found.Signal/Noise (S/N) rates were found with using the Taguchi method. According tothe results, feed rate had the most significant effect on Rz among threefactors. In ANOVA analysis, respectively feed rate, cutting depth and cuttingspeed are effective at 95% confidence level at Rz value. In repetitionexperiments carried out for parameters chosen in Taguchi prediction, it wasidentified that Taguchi works with nearly 94% accuracy.